Postoperative alkaline reflux gastritis: Aetiopathogenic, diagnostic and therapeutic considerations - Carriquiry, Luis A.; Bergalli, Luis E. (Cirugía del Uruguay, 1982)
This type of gastritis has become a real entity within the complex range of the "operated stomach syndrome" in the past few years.